2019
DOI: 10.3390/ijerph16030471
|View full text |Cite
|
Sign up to set email alerts
|

Exposure Characterization of Haloacetic Acids in Humans for Exposure and Risk Assessment Applications: An Exploratory Study

Abstract: Disinfected water is the major source of haloacetic acids (HAAs) in humans, but their inter- and intra-individual variability for exposure and risk assessment applications is under-researched. Thus, we measured HAAs in cross-sectional and longitudinal urine and water specimens from 17 individuals. Five regulated HAAs—mono, di, and trichloroacetic acid (MCAA, DCAA, and TCAA) and mono- and dibromoacetic acid (MBAA and DBAA)—and one unregulated HAA—bromochloroacetic acid (BCAA)—were measured. Urinary DCAA, MBAA, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
7
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 30 publications
(7 citation statements)
references
References 62 publications
0
7
0
Order By: Relevance
“… 30 Although the results of previous studies that applied THMs in blood or urine as internal biomarkers of DBP exposure cannot be directly compared with our results, urinary HAA biomarkers measured by TCAA have been reported to reflect ingestion of chlorinated THM and HAA exposures in drinking water. 54 , 55 The present findings suggest that exposure to DBPs may have adverse effects on liver function.…”
Section: Discussionmentioning
confidence: 49%
See 1 more Smart Citation
“… 30 Although the results of previous studies that applied THMs in blood or urine as internal biomarkers of DBP exposure cannot be directly compared with our results, urinary HAA biomarkers measured by TCAA have been reported to reflect ingestion of chlorinated THM and HAA exposures in drinking water. 54 , 55 The present findings suggest that exposure to DBPs may have adverse effects on liver function.…”
Section: Discussionmentioning
confidence: 49%
“… 62 In addition, previous studies have shown that urinary TCAA is significantly correlated with ingestion of THMs and TCAA in drinking water. 54 , 55 , 63 However, there was a null association between urinary TCAA and liver injury. This suggests that ingestion of exposure to THMs may less confound the observed association of urinary DCAA with liver injury.…”
Section: Discussionmentioning
confidence: 97%
“…This finding is directly in line with Smith et al [ 13 ] that showed a significant moderate correlation ( r = 0.50, p value=0.002) between ingested TCAA from home tap water and TCAA in urine as well as by Zhang et al [ 12 ] showing a significant strong correlation ( r = 0.66, p value < 0.001). On the contrary, some other studies did not report statistically significant correlations between urine and ingested TCAA from drinking water [ 10 , 11 , 49 , 53 ]. All previous studies highlighted that the assessment of water consumption is the basis of measuring TCAA exposure variability whereas individual volume of tap water, source, behavioral differences and employment status are key factors that explain this variability.…”
Section: Discussionmentioning
confidence: 91%
“…Our findings showed that TCAA was the most prevalent HAA in urine (69.2% >LOD; non-adjusted >LOD: mean = 4.2 μg/L, median = 1.3 μg/L; creatinine adjusted >LOD: mean = 3.0 μg/g, median = 1.3 μg/g. Comparable levels of mean urinary unadjusted TCAA concentrations were observed in the US general population sample (3.3 µg/L) [ 49 ] and in a sample of Chinese pregnant women (2.7 µg/L) [ 50 ]. However, higher concentrations have been reported in a UK sample of pregnant women (unadjusted mean = 6.1 µg/L) [ 13 ].…”
Section: Discussionmentioning
confidence: 99%
“…Nephrotoxity and urogenital tract dysfunction are established pathological outcomes of chlorination stress. Among other pathologies, acute kidney injury, glomerulonephritis, diabetic nephropathy, and bladder cancer have been associated with exposure to pathological chlorination stress (110,(162)(163)(164)(165)(166).…”
Section: Human Target Organs Of Environmental Chlorination Stressmentioning
confidence: 99%